Impaired SREBP1-mediated regulation of lipid metabolism promotes inflammation in chronic endometritis - Matsuda, Shigeru; Kuwabara, Yoshimitsu; Taketomi, Yoshitaka; Nagasaki, Yuki; Sugita, Yosuke; Suzuki, Shunji; Manabe, Ichiro; Murakami, Makoto; Oishi, Yumiko (Frontiers in Immunology, 2025)
Chronic endometritis (CE) is an inflammatory disease of the uterus that is associated with infertility and poor reproductive outcomes. Although most cases of CE are attributed to bacterial infections, antibiotic treatment is sometimes ineffective, and the mechanisms underlying the development and persistence of inflammation in CE are poorly understood. In the present study, we established a novel mouse model of CE that causes fetal death without affecting implantation and demonstrated that dysregulation of lipid metabolism contributes to its pathology. A deficiency in SREBP1, a key regulator of lipid metabolism, prolonged endometrial inflammation with CD138+ plasma cell accumulation and induced miscarriage in LPS-induced endometritis, thereby mimicking CE. Lipidomic analyses showed that Srebf1 deficiency significantly reduced phospholipids containing eicosapentaenoic acid (EPA) within uterine tissue. Dietary supplementation of EPA increased endometrial levels of EPA-containing phospholipids and ameliorated inflammation and miscarriage in Srebf1-/- CE mice. These results suggest that dysregulation of lipid metabolism, particularly reductions in polyunsaturated fatty acids in endometrial phospholipids, promotes inflammation and miscarriage in CE. Importantly, EPA-containing phospholipids were also decreased in endometrial tissue from human CE patients. Thus, dysregulated lipid metabolism appears to play a pivotal role in the development of CE and provides novel therapeutic targets.